Shift in the Role of HR Professionals: Critical Trends in HR Management Practices - Jain, Ms. Aditi (International Research Journal of Management, IT & Social Sciences, 2016)
The business world is concerned with improvement of organizational performance. Consequently, Human Resource Management (HRM) practices outcome on organizational performance has been the major concern of the previous scholars. Therefore, any organization that fails to improve its performance would not be able to meet up with trends in achieving competitive advantages. HR means understanding the implications of globalization, work-force diversity, changing skill requirements, corporate downsizing, continuous improvement initiatives, re-engineering, the contingent work force, decentralized work sites and employee involvement. Organizations today are also witnessing a change in system, management cultures and philosophy due to the global alignment .There is a need for multi skill development and the role of HRMÂ  is becoming all the more importantÂ